Media Pembelajaran Hidden Curriculum terhadap Pendidikan Anti Korupsi - Dian Indriana Hapsari; St. Dwiarso Utomo; Entot Suhartono (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
The purpose of this study is to find out about the role of hidden curriculum learning media regarding the anticorruption education. The problem is focused on the level of undergraduate student’s interest in prevention and eradication of corruption in Indonesia through anticorruption hidden curriculum taught at college. Datas are collected by interview with final semester undergraduate students as the sample, observation, and documentation technique to be analyzed qualitatively. The result of this study shows that hidden curriculum as learning media regarding anticorruption education is taught and responded differently by each students. It is concluded that most students are interested in the corruption problem and support the efforts to eradicate corruption. The obstacle is the lack of student ability to organize regarding to prevent and eradicate corruption.